MONETARY INDICATORS OF THE STABILITY OF PRICES - Dewi Mahrani Rangkuty; Bakhtiar Efendi; Antonius Gulo (Proceeding of The International Conference on Economics and Business, 2022)
This study aims to analyze the contributions of the variable interactions of monetary policy in the stability of goods and services prices. Where is the monetary policy variable (inflation, kurs, consumer price index, gross domestic products, the money supply, and interest rates). Research in conducted in the country of Indonesia and uses secondary data or time series from 2008 to 2021. The data analysis model in this study is Simultaneous Model. Simultaneous equations to analyze the relation between independent and variable variables found in the research country. Simultaneous analysis of equations on statistical test common equation 1 suggests that variable interest rates, money distribution, exchange rates and consumer price indexes have significant adverse effects on the inflation. Whereas in the same equation 2, it suggests that gross domestic product variables have a positive relationship that is significant to the ihk. And inflation has a negative relationship significantly insignificant to consumer price index. For this reason, the researcher hopes that the monetary authority, namely Bank Indonesia, can improve monetary stability and maintain the BI rate in regulating the money supply so that it can suppress the inflation rate as an effort to stabilize the prices.